Calcium promotes differentiation in ameloblast-like LS8 cells by downregulation of phosphatidylinositol 3 kinase /protein kinase B pathway. (January 2020) - Gao, Jianghong; Gao, Zhen; Dang, Fan; Li, Xinmei; liu, Hao; Liu, Xiaojing; Gao, Meili; Ruan, Jianping
Highlights: Calcium induced S phase arrest and regulatory protein changes in LS8. Calcium enhanced KLK4 and AMTN expressions in LS8. Calcium inhibits PI3K/AKT signaling in LS8. Abstract: Objectives: To investigate the effect and mechanism of calcium on LS8 cell differentiation, especially on phosphatidylinositol 3 kinase (PI3K) /protein kinase B(AKT) pathway. Materials and methods: Ameloblast-like LS8 cell line was used and additional 0–3.5 mmol/L calcium chloride was treated for 24 h, 48 h. Cell viability and morphological changes, cell cycle and associated regulatory proteins were analyzed. Results: No significant effects on morphological changes were observed. Decreased cell viability and increased S phase cells were accompanied by the significant decrease of cyclin A and cyclin B proteins, and significant increase of cyclin D protein in LS8 cells. Additionally, kallikrein-4 and amelotin expressions were significantly increased. Finally, the levels of PI3K, AKT, p-AKT and forkhead box O3 (FOXO3) significantly downregulated after calcium treatment in LS8 cells. Conclusions: Calcium inhibit proliferation and promotes differentiation in LS8 cells, this is closely related to the downregulation of PI3K/AKT signal in LS8 cells.